Latent Class Analysis of School Refusal Behavior and Its Relationship With Cyberbullying During Adolescence - Delgado, B.; Martinez-Monteagudo, M. C.; Ruiz-Esteban, C.; Rubio, E. (Frontiers in Psychology, 2019)
Cyberbullying is a common relational problem having negative repercussions on the academic performance of adolescents. Numerous questions remain to be answered with regards to the relationship between cyberbullying and school refusal behaviour. This study examines school refusal profiles (measured by School Refusal Assessment Scale-Revised) and assesses whether these profiles vary with respect to the level of victimization, aggression, aggression-victimization and observation of cyberbullying (measured with the Screening of Harassment among Peers). The sample consisted of 1102 Spanish high school students, aged 12 to 18 (M = 14.30, SD = 1.71). Latent class analysis revealed three school refusal behaviour profiles: non-school refusal behaviour, school refusal behaviour by negative reinforcements (oriented to the avoidance of social evaluation and negative affectivity in school situations), and school refusal behaviour by positive reinforcements (oriented to obtaining the attention of others with significant or tangible reinforcements). The ANOVA found statistically significant differences for all cyberbullying behaviors. Students with school refusal by negative reinforcements had significantly higher mean scores as compared to the other profiles in victimization, aggression, aggression-victimization and observation behaviors, while the levels of cyberbullying were similar between students without school refusal and students with school refusal behaviour by positive reinforcements. These findings underscore the need to consider priority interventions to prevent cyberbullying in children who refuse school for the purpose of avoiding situations of anxiety and negative emotions.